North by 2020 : perspectives on Alaska's changing social-ecological systems - Lovecraft, Amy Lauren; Eicken, Hajo (University of Alaska Press, 2011)
Originating from a series of workshops held at the Alaska Forum of the Fourth International Polar Year, this interdisciplinary volume addresses a host of current concerns regarding the ecology and rapid transformation of the arctic. Concentrating on the most important linked social-ecological systems, including fresh water, marine resources, and oil and gas development, this volume explores opportunities for sustainable development from a variety of perspectives, among them social sciences, natural and applied sciences, and the arts. Individual chapters highlight expressions of climate change.